PENYULUHAN TENTANG KOMUNIKASI KELUARGA DALAM MENCEGAH KENAKALAN REMAJA - Soemardjo, Herta Armianti; Haniza, Nurul; Liana, Chendi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The month of Ramadhan is expected to be the moment for Moslems to carry out religious and good deeds. In this holy month. In line with this momentum, in Ramadhan 2024, our team – the team of Community Service Program from Sahod University, together with other Community Service teams carried out a community service program in the form of an educational program about Family Communication at the Kelurahan Cililitan, East Jakarta. This program was to express our concern and care towards the community’s problems by distributing food and organizing educational program to prevent and suggesting solution to juvenile delinquincies. This program was held on April 3rd, 2024, at the auditorium of Ruang Publik Terpadu Ramah Anak (RPTRA) Cicilitan, East Jakarta. There were 60 participants, who consisted of cadre, yang terdiri dari kader, public figure and residents of the Cililitan village, East Jakarta. The activity started with a main material about “Building a Healthy Family: which were continued with distribution of food supplies. This program was warmly accepted by all participants and the Head of Village and RPTRA, and they addressed their hope that it could be an ongoing program.